SGLT2 inhibitors across various patient populations in the era of precision medicine: the multidisciplinary team approach - Patrick McLean; Josiah Bennett; Edward “Trey” Woods; Sanjay Chandrasekhar; Noah Newman; Yusuf Mohammad; Muzamil Khawaja; Affan Rizwan; Riyan Siddiqui; Yochai Birnbaum; Carl J. Lavie; Salim Virani; et al. (npj Metabolic Health and Disease)
Abstract Sodium-glucose cotransporter-2 inhibitors have revolutionized the management of a variety of diseases. Initially developed to address glycemic control in diabetes, sodium-glucose cotransporter-2 inhibitors were identified for their ability to inhibit glucose reabsorption in the kidneys. Landmark trials for highly selective agents demonstrated cardioprotective and renoprotective effects of sodium-glucose cotransporter-2 inhibitors, leading to expanded indications for use in both heart failure with reduced ejection fraction and heart failure with preserved ejection fraction. Sodium-glucose cotransporter-2 inhibitors are now approved for a variety of clinical indications, including heart failure, chronic kidney disease, and type 2 diabetes mellitus, with increasing interest in management of steatotic diseases of the liver and weight loss. Despite this, the adoption of the drug class into clinical practice remains suboptimal, hindered by cost and clinician familiarity. This review explores the therapeutic indications for sodium-glucose cotransporter-2 inhibitors, examining their mechanisms of action, classic and prospective clinical effects, safety profile, and impact on decision-making, while highlighting emerging evidence for additional applications such as weight loss, anti-hypertensive, and anti-steatotic effects.